Case of Retail Business X in North of Bekasi: The Effect of Training on Performance Mediated by Motivation - Rycha Kuwara Sari; Kardinah Indrianna Meutia; Bintang Narpati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study was used to measure the effect of training on Performance mediated by motivation in retail businesses. This research is quantitative research where the object used is an employee in a retail business. This research was conducted using a non-probability sampling technique with a purposive sampling method. The number of samples used in this study was 60 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 3.0. The results of this study provide an explanation that the training variable affects employee performance in retail businesses, training affects motivation, motivation affects employee performance in retail business and training affects the Performance of retail business employees mediated by motivation. This research has a limited object of research which is only conducted on retail business employees. This is used as a suggestion for future researchers. The novelty of this study combines training variables on Performance mediated by motivation in the retail business.